ENHANCING DIGITAL INCLUSION IN MULTILINGUAL EDUCATION: EXPLORING THE ROLE OF TECHNOLOGY IN SOUTH AFRICAN HIGHER EDUCATION - Zanele Priscila Msweli; Oluwatoyin Ayodele Ajani (International Journal of Innovative Technologies in Social Science, 2024)
The Fourth Industrial Revolution has significantly impacted teaching and learning in higher education worldwide. However, many developing countries have continued to face challenges in embracing digital transformation within their education systems. This study explored strategies to enhance digital inclusion through multilingual education, focusing on South Africa and the integration of technology into multilingual learning environments. The Technology Acceptance Model (TAM) was used to understand how digital tools could be successfully incorporated into multilingual education to improve access and inclusion. A systematic review of relevant literature was conducted, drawing from databases such as Scopus and Google Scholar, focusing on studies published between 2020 and 2024. Thematic analysis was used to identify key themes from 72 articles, published in English language and in peer-reviewed journals, which informed the findings and recommendations. The study aimed to offer practical strategies for improving digital literacy and inclusion in multilingual education, particularly in developing countries. The results provided valuable insights for policymakers, educators, and stakeholders, offering ways to promote equity and access to digital resources in multilingual learning environments.